Introduction to Special Topic: Serving Children With Disabilities Within Multitiered Systems of Support - Brett Miller; Katherine Taylor; Ruth E. Ryder (SAGE Publishing, 2019)
Since the conception of the Education for All Handicapped Children Act in 1975, there has been substantial progress regarding the education of learners with disabilities. Nevertheless, significant challenges remain for addressing the diverse needs of these learners and improving in- and out-of-school outcomes. This special topic focuses on an approach that holds promise for the delivery of interventions that are aligned to learners' social, emotional, behavioral, and learning needs-multitiered systems of support (MTSS). The four articles that comprise the special topic highlight the need for actionable information for schools implementing MTSS, early intervention for children with or at risk for disabilities, and an enhanced focus on intensive interventions. This introduction to the special topic provides information on the meeting that motivated the special topic, a summary of each of the four articles, and paths forward for early and sustained intervention for learners with or at risk for disabilities.